Pediatric Herniotomy: A 2-year Follow-up Study at Nepal Medical College and Teaching Hospital - Pradhan, Giridhar Bahadur Nhuchhe; Shrestha, Sunil; Chalise, A; Shrestha, S (Nepal Medical College Journal, 2021)
Repair of inguinal hernia is one of the most commonly performed pediatric surgical procedures. The standard of treatment has been open herniotomy (OH). Recent trends have shown promising results with use of laparoscopy (LH) for the same. The aim of this study was to compare laparoscopic herniotomy with the standard of care at the time of the study, which has become an increasingly common procedure at our center. This was a prospective follow-up study conducted at the Department of Surgery at Nepal Medical College and Teaching Hospital. A total of sixty-four patients who underwent herniotomy were included in the study and followed up for a total duration of two years post-operatively. Immediate post-op pain was assessed with the use of visual analogue scales. Complications, recurrence, and metachronous herniation were noted in the follow up visits. Use of laparoscopy resulted in a longer operative time (36.68 min vs 22.5 min for OH, P <0.001). Pain scores were similar at immediate post-op period (LH 4.18 vs OH 3.93) but decreased significantly for LH compared to OH at 6 hours (3.68 vs 4.31, P = 0.018), 12 hours (2.71 vs 3.62, P <0.001), and 24 hours (2 vs 3.03, P <0.001). Difference in the mean hospital stay was statistically significant (LH 2.02 days vs OH 2.34 days, P <0.001). No recurrences occurred during the follow up period of the study. No patients developed contralateral metachronous hernia during the follow-up period. The cost of OH compared to LH was significantly less. LH is a safer and better alternative to OH for management of pediatric inguinal hernia when comparing post-op pain and hospital stay. However, duration of surgery and cost for the procedure favor OH at present in our setup.